Effective patient-provider communication in healthcare genetics: a concept analysis - Cotter, Jennifer D.; Jones, Karyn O.; Davis, Stephanie C.; Baker, Anna; Koci, Anne; Boccuto, Luigi (Frontiers in Communication, 2024)
Effective communication of genetic testing results between healthcare providers and patients remains essential, but the concept generally lacks a precise definition. Since clinical genetic testing has increased dramatically in recent years, it is crucial to clarify the concept of effective communication as it pertains to patient-provider communication in healthcare genetics. The Walker and Avant methodology of concept analysis was used to operationalize the effective communication definition, along with the identification of associated characteristics and illustrative examples of the concept's application. This refined definition informs communication in healthcare genetics practice and supports the development of future research methodologies for assessing the effectiveness of communication approaches in clinical genetics.